Conversor CC-CC bidirecional em corrente para aplicação em veículos elétricos - Barrozo, Francisco Eudes Oliveira (2010)
This work presents study of a DC-DC converter based on three states switching cell for application in Electric Vehicles (EVs). The converter is designed to operate in two modes: step up mode (boost) and step down mode (buck). The presented topology enables the bidirectionality of energy, with situations that is returned by the bus load formed by a group of batteries. A quantitative and qualitative analysis converter is done, the converter is designed for a output power of 10 kW, assuming a linear load. It is further performed a modeling and control study for the boost mode of operation in order to obtain a voltage bus to drive a traction motor of electric vehicle. To verify the working principle of the converter, was implemented in laboratory a prototype of 1 kW.